2021
DOI: 10.1371/journal.pone.0255819
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, government measures and hospitality industry performance

Abstract: This study explores the interplay between public measures adopted by the U.S. government to combat COVID-19 and the performance of the American hospitality industry. The recent global pandemic is a natural experiment for exploring the role of government interventions and their direct impact on hospitality stock returns in the U.S. financial market. Overall, our findings show that most of the government interventions were associated with a negative response in the returns of the hospitality industry, a response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…We find evidence that government intervention can have a moderating effect on the impact of COVID‐19 on firm performance. The result is in line with Aharon et al ( 2021 ), wherein they document that government intervention to control the pandemic had a more adverse effect on firms belonging to a few sectors. Further, Shen et al ( 2020 ) also found that the impact of the coronavirus pandemic on performance was greater for firms operating in high‐impact industries as their operations were affected due to government restrictions.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We find evidence that government intervention can have a moderating effect on the impact of COVID‐19 on firm performance. The result is in line with Aharon et al ( 2021 ), wherein they document that government intervention to control the pandemic had a more adverse effect on firms belonging to a few sectors. Further, Shen et al ( 2020 ) also found that the impact of the coronavirus pandemic on performance was greater for firms operating in high‐impact industries as their operations were affected due to government restrictions.…”
Section: Resultssupporting
confidence: 89%
“…On the contrary, Jiang et al ( 2014 ) find that firms bailed out by the government during GFC had lower recovery rates than those bailed out by other stakeholders of firms. More recently, Aharon et al ( 2021 ), in their study of the US hospitality industry find that government intervention during the coronavirus pandemic was negatively related to stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a survey of forty-six countries, Villacé-Molinero et al (2021) concluded that in the context of a pandemic, the trust in the local government's messages about personal safety was the principal consideration for visitors in making travel decisions. However, communication from the U.S. government is also found to be a source of uncertainty and mistrust throughout the COVID-19 pandemic ( Aharon et al, 2021 ). Thus, Americans' confidence in governmental advisory and their international travel intentions is a valuable topic that must be explored in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of international trips taken by Americans decreased by 66.4% in 2020, compared to the same twelve-month period in 2019 ( Hepple, 2021 ). The uncertainty associated with the pandemic itself was exacerbated by the uncertainty in American government communications, resulting in financial consequences to tourism and hospitality ( Aharon et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the policy was aimed at encouraging an increase in tourist visits, the recovery of the tourism sector and an increase in the productivity of economic enterprises. Thus, policy support from the government is needed in order to avoid economic bankruptcy, particularly in small and medium enterprises (SMEs), and it can be implemented by strengthening technological capabilities and investment support [78,79].…”
mentioning
confidence: 99%